SINISME MEMPENGARUHI KINERJA SEBUAH ORGANISASI DENGAN MODERASI EMPOWERING LEADERSHIP: Cynicism Affects the Performance of an Organization with Empowering Leadership Moderation - James Bryan; Dr. Teofiuls S.M., M.M (Jurnal Performa : Jurnal Manajemen dan Start-up Bisnis, 2022)
The purpose of this research is to find out the effect of cynicism on the performance of an organization by empowering leadership moderation. The population in this research is the employees who work in food and beverage field in West Surabaya. This research technique is random sampling technique with the total sample of 212 respondents. Data that is obtained in this research is primary data by distributing questionnaires through google forms. This research is quantitative research. Based on the result of the research, the cynicism factor in this research does not affect organizational performance of employees who work in the food and beverage field. Secondly, the empowering leadership factor does not moderate the relation between cynicism and the organizational performance of employees who work in the food and beverage field. The cynicism variable in companies is very difficult to be analyzed in Indonesia, because Indonesian culture has reluctant attitude. This reluctant attitude causes the cynicism variable in this research does not give any effect on organizational performance. This statement supports the result of the research from empowering leadership variable does not moderate the relation of cynicism on organizational performance. This research finds out new hypotheses in which empowering leadership affects directly on organizational performance.